The Nikkei women in Peru - Morimoto Hayashi, Amelia (2019)
This article is an approach to the topic of the immigration and the community of the Japanese origin in Peru from the gender perspective, in which stands out especially the case of immigrant women of Japanese and their descendants Peruvian Japanese origin or “Nikkei”.